Longitudinal study of HIV protease mutations in oral tissues of selected patients - Peter J. Hickman; Janet E. Leigh; Paul L. Fidel. Jr; Ronald B. Luftig (Universidade Estadual de Campinas, 2015)
Twenty-nine HIV-1 infected patients from New Orleans were enrolled as a cohort for this study over a four and one half year period. HIV-1 protease gene (pro) sequences were amplified using DNA isolated from oral tissues (gingival cuff, buccal mucosa, tongue, palate) as well as saliva and peripheral blood mononuclear cells (PBMC). PCR products were directly sequenced using a combination of manual and automated methods, and nucleotide sequences were translated using the universal genetic code. Protein sequences obtained from independent amplifications of a particular patient at a given time were consolidated into a single consensus sequence and compared to HIV-1LAI to determine amino acid replacements. The major findings were: 1) each patient had a signature sequence that probably represented the predominant HIV-1 quasispecies; 2) over periods of 19 to 1673 days mutation patterns remained relatively stable within a given patient; and 3) although nearly 40% of the initial nonsynonymous replacements in the protease signature sequences were mutations known to impart resistance to protease inhibitors (PI), over time patients did not accumulate additional PIR mutations